The Influence of Dynamic Capabilities, Entrepreneurial Orientation, and Quality of Strategy on Increasing Business Performance (Empirical Study on Batik MSMEs in Semarang City) - Shofwani, Siti Aniqoh; Santoso, Aprih; Armiella, Adestya Ayu; Wahdi, Nir Setyo; Nurhidayah, Fitriyah (JURNAL BISNIS STRATEGI, 2023)
This study aims to examine and analyze the effect of dynamic capabilities, entrepreneurial orientation, and strategic quality on improving business performance (Empirical Study on Batik SMEs in Semarang City). The 3,256 MSME actors are the population. The 97 respondents selected were batik MSME actors who were active for a period of 5 years. The dynamic capability variable partially has a positive and significant effect on business performance. This is evidenced by the value of the regression coefficient value of 0.231 (positive) with a significance value of 0.000 <0.05, then H1 is accepted. The entrepreneurial orientation variable partially has a positive and significant effect on business performance. This is evidenced by the regression coefficient value of 0.345 (positive) with a significance value of 0.000 <0.05, then H2 is accepted. The strategic quality variable partially has a positive and significant effect on business performance. This is evidenced by the value of the regression coefficient of 0.179 (positive) with a significance value of 0.014 <0.05, then H3 is accepted. The variables of dynamic capability, entrepreneurial orientation and strategic quality simultaneously affect business performance. This is evidenced by the calculated F value of 14.328 > F table of 3.09 and a significance value (Sig.) 0.000 <0.05, then H4 is accepted.